Examining Employee Work Motivation With Daily Travel Allowance as a Trigger - Harsudi, Hidayat; Alam, Syamsu; Tenriwaru, Tenriwaru (Economos : Jurnal Ekonomi dan Bisnis, 2024)
Work motivation is the drive or reason that pushes someone to perform their job well. Work motivation is important because it directly influences an individual’s performance, productivity, and job satisfaction. This research aims to determine the work motivation of employees at the South Sulawesi Railway Management Center (BPKASS) triggered by daily travel allowance incentives. Daily travel allowance is the money received by employees while carrying out official duties. This allowance includes meal money, local transportation expenses, and pocket money used by employees to meet their needs while on duty. This research uses a qualitative method with an interpretive paradigm. The type of research is a case study using interview, observation, and documentation techniques with BPKASS employees. The results show that the daily travel allowance increases the income of BPKASS employees due to the lump sum payment of the allowance. The income is derived from the difference between the daily allowance used and the daily allowance received by employees while performing their duties. The factors that determine the amount of income earned from the daily allowance include the type of official travel activities attended, the number of days of execution, and the location of the official travel activities. The daily travel allowance serves as a work motivation trigger because employees receive additional income besides their salary and allowances.